Thermoplastic composition for laser direct structuring
By adding copper chromium spinel laser direct structure additives, flame retardants and acid modified polymers to the aromatic polycarbonate composition, the problems of insufficient softening temperature, high viscosity and poor flame retardancy in high-temperature applications are solved, and a composition with high strength, low viscosity and excellent flame retardant properties are achieved.
Patent Information
- Application Number
- CN202380051463.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-05
- Filing Date
- 2023-07-05
- Publication Date
- 2025-03-04
AI Technical Summary
In high-temperature applications, existing aromatic polycarbonate compositions have problems such as insufficient softening temperature, high melt viscosity, difficulty in filling the wall thickness and poor flame retardancy, especially in parts that require welding.
The composition using a combination of flame retardant and acid modified polymer is reduced melt viscosity and improved flame retardant performance by combining the application of flame retardant and acid modified polymer.
The high VIKA softening temperature of the composition, good cantilever beam notch impact strength and excellent flame retardant properties are achieved, and are suitable for the production of thin-walled molded products with conductive rails.
Smart Images

Figure BDA0005224336910000081 
Figure BDA0005224336910000091 
Figure BDA0005224336910000092
Abstract
Description
Technical Field
[0001] The present invention relates to a thermoplastic composition comprising an aromatic polycarbonate and a copper-chromium spinel laser direct structuring additive, a molding comprising the composition, a method for producing a circuit carrier using the molding, and a circuit carrier obtained by the method. Background Art
[0002] For example, US-B2-7060421 and WO-A-2009024496 describe a polymer composition comprising a polymer and a laser direct structuring (LDS) additive which can be activated by laser radiation to form elemental metal nuclei. Such a polymer composition can be advantageously used in an LDS process for producing non-conductive parts by irradiating areas of the part with laser radiation to activate the plastic surface where the conductive paths are located, decomposing the laser direct structuring additive and releasing the metal nuclei, and subsequently metallizing the irradiated areas to accumulate metal on these irradiated areas, thereby forming conductive tracks on the non-conductive part.
[0003] Aromatic polycarbonate compositions are described in WO-A-2009024496, which contain metal compounds that can be activated by electromagnetic radiation and thereby form elemental metal cores and 2.5-50% by weight of rubbery polymers, the latter being added to reduce the degradation of polycarbonate caused by the presence of such metal compounds in the aromatic polycarbonate compositions. However, in some applications, particularly high temperature applications, the presence of a large amount of rubbery polymers is disadvantageous, such as parts that require welding. For such applications, a higher softening temperature, such as a temperature expressed as the Vicat softening temperature, is required. In addition, the presence of rubbery polymers leads to high viscosity, which is incompatible with modern demands, which require objects made from these compositions to have thin walls, such as having a wall thickness of ≤1.5 mm, or even ≤1 mm. Therefore, the flow properties of these compositions should be sufficient to fill thin-walled molds. In practice, this requires appropriately low melt viscosity values. Finally, some rubbery polymers and excessive amounts of rubbery polymers reduce the flame retardancy of articles made from these compositions, which is also undesirable.
[0004] However, as shown in WO-A-2009024496, compositions comprising aromatic polycarbonate and laser direct structuring additives, but containing no or only a small amount of rubbery polymer, are susceptible to polycarbonate degradation, which results in reduced toughness, for example as manifested in the notched Izod impact strength of molded articles made from the composition. Summary of the invention
[0005] It is therefore an object of the present invention to provide an aromatic polycarbonate composition comprising a laser direct structuring additive but containing no or only a small amount of rubbery polymer, which composition has improved toughness and a sufficiently high softening temperature.
[0006] Another object of the present invention is to provide an aromatic polycarbonate composition comprising a laser direct structuring additive, the composition having excellent melt flow properties.
[0007] Finally, flame retardancy is important. It is therefore a further object of the present invention to provide an aromatic polycarbonate composition which allows the production of molded articles having conductive tracks which have good flame retardancy. DETAILED DESCRIPTION
[0008] Therefore, the present invention provides a thermoplastic composition, comprising:
[0009] a) 85-95% by weight of aromatic polycarbonate;
[0010] b) 2-15 wt. % of a copper chromium spinel laser direct structuring additive;
[0011] c) 0.05-5 wt% of a flame retardant, wherein the flame retardant is a flame retardant salt or an organic flame retardant;
[0012] d) 0.1-2 wt% of an acid-modified polymer;
[0013] e) Optional 0-5 wt% of a silicon modifier.
[0014] The amounts of components a), b), c), d) and e) are based on the total weight of the thermoplastic composition.
[0015] Surprisingly, it has been found that the combination of components c) and d) in an aromatic polycarbonate (sometimes referred to herein as PC) composition containing a copper chromium spinel laser direct structuring additive (sometimes referred to herein as LDS additive) can bring about a suitable melt viscosity. Therefore, the composition has good processability and is suitable for producing thin-walled products; at the same time, the molded products made from the composition have good Izod notched impact strength, high Vicat softening temperature and excellent flame retardant properties.
[0016] The composition according to the invention can be formed into a moulding and can be provided therewith with conductive tracks by laser irradiation and a subsequent metallisation step.
[0017] Therefore, the present invention further relates to a molded article comprising the thermoplastic composition according to the invention. The present invention particularly relates to a molded article produced by injection molding using the composition according to the invention. The present invention further relates to an article, in particular a circuit carrier, comprising a molded article produced from the composition according to the invention and conductive tracks provided on the molded article. In one embodiment, such a circuit carrier is used to produce an antenna.
[0018] The present invention further relates to a method for producing the above-mentioned circuit carrier, which method comprises the following steps: providing a molded article comprising a thermoplastic composition according to the present invention, irradiating the area on the molded article where the conductive track will be formed with laser radiation, and then metallizing the irradiated area. In a preferred embodiment, the laser radiation is used to simultaneously release the metal core and achieve a component ablation effect, while forming a surface that promotes adhesion. This provides a simple method to achieve excellent adhesion strength of the deposited metal conductor track. The wavelength of the laser is preferably 248nm, 308nm, 355nm, 532nm, 1064nm or even 10600nm. The process of further depositing metal on the metal core generated by laser radiation is preferably carried out by an electroplating process. The metallization treatment is preferably carried out by immersing the molded article in at least one electroless plating bath to form a conductive path in the irradiated area of the molded article. Non-limiting examples of electroless plating processes include copper plating processes, gold plating processes, nickel plating processes, silver plating processes, zinc plating processes and tin plating processes. Preferably, the first coating is copper plating. The conductive track can have one or more layers. The first layer may be, for example, a copper layer, and may have a thickness of 8-16 μm, more typically 8-12 μm. If a second layer is present, the second layer may be, for example, a nickel layer, and may have a thickness of 2-4 μm. If a third layer is present, the third layer may be, for example, a gold layer, and may have a thickness of 0.05-0.2 μm.
[0019] The radiation treatment of the molded article may be performed under conditions including, for example, a power of 2-15 W, a frequency of 20-100 kHz, and a speed of 1-5 m / s.
[0020] The irradiation treatment of the molded article can be carried out by, for example, ultraviolet light (wavelength of 100 to 400 nm), visible light (wavelength of 400 to 800 nm) or infrared light (wavelength of 800 to 25000 nm). Other preferred radiation forms include X-rays, gamma rays and particle beams (electron beams, α-particle beams and β-particle beams).
[0021] When the molded article is irradiated with ultraviolet rays having a wavelength of 100 to 400 nm, the molded article having the metallized area is preferably heat treated to improve its resistance to delamination. The heat treatment can be achieved by subjecting the molded article to microwave treatment, for example, by placing the molded article in a microwave oven. Preferably, the molded article is irradiated with visible light having a wavelength of 400 to 800 nm, infrared rays having a wavelength of 800 to 25000 nm, X-rays, gamma rays or particle beams. The advantage of these types of laser radiation is that the metal layer in the irradiated area has a relatively strong adhesion strength without the need for heat treatment after the plating step.
[0022] More preferably, the molded article is irradiated with visible light having a wavelength of 400 to 800 nm or infrared light having a wavelength of 800 to 25000 nm. Most preferably, the molded article is irradiated with infrared light having a wavelength of 800 to 25000 nm.
[0023] Preferably, the method for producing a circuit carrier does not include a step of heat treatment after the step of metallizing the irradiated areas. This is advantageous in order to increase the efficiency of the process.
[0024] Preferably, the molded article made from the composition of the present invention can achieve UL94 V1 or V0 rating at a thickness of 1.5 mm (±10%). More preferably, the molded article made from the composition of the present invention can achieve UL94 V0 rating at a thickness of 1.5 mm (±10%).
[0025] Preferably, according to ASTM D 3835, at 300°C and 1500s -1 Under the conditions of 300°C and 1500s, the melt viscosity of the composition is less than 230Pa.s, more preferably less than 210Pa.s, and even more preferably less than 190Pa.s. Preferably, according to ASTM D3835 standard, at 300°C and 1500s -1 Under the conditions, the melt viscosity of the composition is greater than 40 Pa.s, more preferably greater than 70 Pa.s, most preferably greater than 100 Pa.s.
[0026] Preferably, the molded article made of the composition according to the invention, optionally provided with conductive tracks produced by laser irradiation and subsequent metallization, has an Izod notched impact strength at 23°C (measured according to ISO 180 / 4A standard, with a sample thickness of 3.2 mm or less) higher than 60 kJ / m 2 , more preferably higher than 65 kJ / m 2 , even more preferably above 70 kJ / m 2 Usually, this value is less than 90kJ / m 2 or 80 kJ / m2 .
[0027] Preferably, the molded article made of the composition according to the invention, optionally provided with conductive tracks produced by laser irradiation and subsequent metallization, has an Izod notched impact strength at -20°C (measured according to ISO 180 / 4A standard, with a sample thickness of 3.2 mm or less) higher than 15 kJ / m 2 , more preferably higher than 20 kJ / m 2 , even more preferably above 25 kJ / m 2 Usually, this value will be lower than 70kJ / m 2 or 60kJ / m 2 .
[0028] Preferably, the molded article made from the composition of the present invention has a Vicat B50 (Vicat softening temperature measured according to ISO 306 standard at a load of 50N and a heating rate of 50°C / h) higher than 130°C, preferably higher than 135°C, more preferably higher than 139°C.
[0029] Particularly preferably, the composition according to the invention:
[0030] -According to ASTM D 3835, at 300°C and 1500s -1 The melt viscosity is less than 230 Pa.s;
[0031] and, a molded article made from said composition, optionally having conductive tracks formed by laser irradiation and subsequent metallization;
[0032] - Izod notched impact strength at -20°C (measured according to ISO 180 / 4A standard with a sample thickness of 3.2 mm or less) higher than 25 kJ / m 2 ;
[0033] - Izod notched impact strength at 23°C (measured according to ISO 180 / 4A standard with a sample thickness of 3.2 mm or less) higher than 70 kJ / m 2 ;
[0034] - Capable of achieving UL94 V0 or V1 rating at a thickness of 3.2 mm (±10%); and,
[0035] - having a Vicat B50 higher than 139°C (measured according to ISO 306 standard at a load of 50 N and a heating rate of 50°C / h).
[0036] Component a)
[0037] The content of a) aromatic polycarbonate in the composition of the present invention is between 85% and 95% by weight, more preferably between 86% and 94% by weight, more preferably between 87% and 93% by weight, and even more preferably between 88 and 92% by weight, relative to the total weight of the composition.
[0038] The aromatic polycarbonate may be an aromatic polycarbonate homopolymer or an aromatic polycarbonate copolymer.
[0039] The polycarbonate comprising aromatic carbonate chain units comprises a component having a structural unit of the following structural formula (I):
[0040] -R 1 -O-CO-O- (I)
[0041] Among them, the group R 1 is an aromatic, aliphatic or alicyclic group. Advantageously, R 1 is an aromatic organic group; and in another embodiment, R 1 is a group of formula (II):
[0042] -A 1 -Y 1 -A 2 - (II)
[0043] Among them, A 1 and A 2 Each is a monocyclic divalent aromatic group, Y 1 is a bridging group having zero, one or two atoms capable of connecting A 1 and A 2 In one exemplary embodiment, one atom separates A 1 and A 2 Examples of such groups include -O-, -S-, -SO-, -S(O2)-, -C(O)-, methylene, cyclohexylmethylene, 2-[2,2,1]-bicycloheptylene, ethylene, isopropylene, neopentylene, cyclohexylene, cyclopentadecylidene, cyclododecylidene, adamantylene, and the like. In another embodiment, zero atoms separate A from 1 and A 2 An example of a bridging group Y is bisphenol. 1 It may be a hydrocarbon group or a saturated hydrocarbon group, such as methylene, cyclohexylene or isopropylene.
[0044] Suitable aromatic polycarbonates include polycarbonates made from at least one divalent phenol and a carbonate precursor, for example, by known interfacial polymerization or melt polymerization methods. Suitable divalent phenols that can be used are compounds having one or more aromatic rings containing two hydroxyl groups, each of which is directly attached to a carbon atom that forms part of the aromatic ring. Examples of such compounds include:
[0045] 4,4'-dihydroxybiphenyl, 2,2-bis(4-hydroxyphenyl)propane (bisphenol A), 2,2-bis-(4-hydroxy-3-tolyl)propane, 2,2-bis-(3-chloro-4-hydroxyphenyl)-propane, 2,2-bis-(3,5-dimethyl-4-hydroxyphenyl)-propane, 2,4-bis-(4-hydroxyphenyl)-2-methylbutane, 2,4-bis-(3,5-dimethyl-4-hydroxyphenyl)-2-methylbutane, 4,4-bis-(4-hydroxyphenyl)heptane, bis-(3,5-dimethyl-4-hydroxyphenyl)-methane, 1,1-bis-(4-hydroxyphenyl)-cyclohexane, 1,1- Bis-(3,5-dimethyl-4-hydroxyphenyl)-cyclohexane, 2,2-(3,5,3',5'-tetrachloro-4,4'-dihydroxydiphenyl)propane, 2,2-(3,5,3',5'-tetrabromo-4,4'-dihydroxydiphenyl)propane, (3,3'-dichloro-4,4'-dihydroxydiphenyl)methane, bis-(3,5-dimethyl-4-hydroxybenzene)-sulfone, bis-4-hydroxyphenylsulfone (bis-4-hydroxyphenylsulphon), bis-4-hydroxyphenylsulphide (bis-4-hydroxyphenylsulphide).
[0046] The carbonate precursor can be a carbonyl halide, a haloformate or a carbonate. Examples of carbonyl halides include carbonyl chlorides and carbonyl bromides. Examples of suitable haloformates include bis-haloformates of divalent phenols (such as hydroquinone) or diols (such as ethylene glycol). Examples of suitable carbonates include diphenyl carbonate, dichlorophenyl carbonate, dibromophenyl carbonate, dialkylphenyl carbonate (di(alkylphenyl)carbonate), phenyltolyl carbonate, etc. and mixtures thereof. Although other carbonic acid precursors may also be used, it is preferred to use carbonyl halides, particularly carbonyl chloride (also referred to as phosgene).
[0047] The aromatic polycarbonate in the composition according to the present invention may be prepared using a catalyst, an acid acceptor and a compound for controlling the molecular weight.
[0048] Examples of the catalyst include tertiary amines (such as triethylamine, tripropylamine, and N,N-dimethylaniline), quaternary ammonium compounds (such as tetraethylammonium bromide), and quaternary phosphorus compounds (such as methyltriphenylphosphonium bromide).
[0049] Examples of the organic acid acceptor include pyridine, triethylamine, dimethylaniline, etc. Examples of the inorganic acid acceptor are hydroxides, carbonates, bicarbonates, and phosphates of alkali metals or alkaline earth metals.
[0050] Examples of the compound for controlling the molecular weight include monovalent phenols (such as phenol, p-alkylphenol, and p-bromophenol) and secondary amines.
[0051] When the aromatic polycarbonate is an aromatic polycarbonate copolymer, the copolymer is preferably a polysiloxane-polycarbonate copolymer.
[0052] Examples of polysiloxane-polycarbonate copolymers are described, for example, in US5380795 and WO09040772, which are incorporated herein as follows:
[0053] The polysiloxane (also referred to as "polydiorganosiloxane") blocks in the copolymer comprise repeating siloxane units (also referred to as "diorganosiloxane units") as shown in formula (1):
[0054]
[0055] Where R can be the same or different each time it appears, and R is C 1-13 For example, R can be independently C1-C 13 Alkyl, C1-C 13 Alkoxy, C2-C 13 Alkenyl, C2-C 13 alkenyloxy, C3-C6 cycloalkyl, C3-C6 cycloalkoxy, C6-C 14 Aryl, C6-C 10 Aryloxy, C7-C 13 Aralkyl, C7-C 13 Aralkyloxy, C7-C 13 Alkaryl, or C7-C 13 The above groups may be halogenated in whole or in part by fluorine, chlorine, bromine, iodine or a combination thereof. Combinations of the above R groups may be used in the same copolymer.
[0056] The value of E in formula (1) can vary widely depending on the type and relative amount of each component in the thermoplastic composition, other factors that need to be considered, such as the desired performance of the composition. Generally, the average value of E can be 2 to 1000, specifically 2 to 500, and more specifically 5 to 100. In one embodiment, the average value of E is 10 to 75, and in another embodiment, the average value of E is 20 to 60. When the value of E is low, such as less than 40, it may be ideal to use a higher amount of siloxane-based rubber in the composition. For example, a composition comprising a polysiloxane-polycarbonate copolymer can include a low content of aromatic polycarbonate and a high content of siloxane-based rubber. On the contrary, when the E value is high, such as greater than 40, the composition comprising a polysiloxane-polycarbonate copolymer needs to include a high content of aromatic polycarbonate and a low content of siloxane-based rubber, or more preferably does not contain siloxane-based rubber.
[0057] A combination of a first and a second (or more) polysiloxane-polycarbonate copolymer may be used, wherein the average value of E of the first copolymer is less than the average value of E of the second copolymer.
[0058] In one embodiment, the polydiorganosiloxane blocks are provided by repeating structural units as shown in formula (2):
[0059]
[0060] wherein E is as defined above; each R may be independently the same or different and is defined above; each Ar may be independently the same or different and is a substituted or unsubstituted C6-C 30 Arylene, wherein the linker is directly attached to the aromatic group. Useful Ar groups in formula (2) can be derived from C6-C 30 Dihydroxyarylene compounds, such as dihydroxyarylene compounds. Combinations comprising at least one of the aforementioned dihydroxyarylene compounds may also be used. Specific examples of dihydroxyarylene compounds include 1,1-bis(4-hydroxybenzene)methane, 1,1-bis(4-hydroxybenzene)ethane, 2,2-bis(4-hydroxybenzene)propane, 2,2-bis(4-hydroxybenzene)butane, 2,2-bis(4-hydroxyphenyl)octane, 1,1-bis(4-hydroxybenzene)propane, 1,1-bis(4-hydroxybenzene)n-butane, 2,2-bis(4-hydroxy-1-tolyl)propane, 1,1-bis(4-hydroxybenzene)cyclohexane, bis(4-hydroxybenzene sulfide) and 1,1-bis(4-hydroxy-tert-butylphenyl)propane. Combinations comprising at least one of the aforementioned dihydroxy compounds may also be used.
[0061] The units of formula (2) may be derived from the corresponding dihydroxy compounds of formula (3):
[0062]
[0063] wherein R, Ar and E are as described above. The compound of formula (3) can be obtained by reacting a dihydroxyarylene compound with, for example, α,ω-diacetoxypolydiorganosiloxane under phase transfer conditions.
[0064] In another embodiment, the polydiorganosiloxane blocks comprise units of formula (4):
[0065]
[0066] wherein R and E are as described above, and each occurrence of R is independently a divalent C1-C 30 In one embodiment, the polydiorganosiloxane blocks are provided by repeating structural units represented by the following formula (5):
[0067]
[0068] Wherein, R and E are as defined above. Each R in formula (5) 5 Each M in formula (5) may be the same or different and may be halogen, cyano, nitro, C1-C8 alkylthio, C1-C8 alkyl, C2-C8 alkoxy, C2-C8 alkenyl, C2-C8 alkenyloxy, C3-C8 cycloalkyl, C3-C8 cycloalkoxy, C6-C8 10 Aryl, C6-C 10 Aryloxy, C7-C 12 Aralkyl, C7-C 12 Aralkyloxy, C7-C 12 Alkyl or C7-C 12 Alkaryloxy, wherein each n is independently 0, 1, 2, 3 or 4.
[0069] In one embodiment, M is bromine or chlorine, alkyl (such as methyl, ethyl or propyl), alkoxy (such as methoxy, ethoxy or propoxy), or aryl (such as phenyl, chlorophenyl or tolyl); R 5 In another embodiment, R is methyl, or a mixture of methyl and trifluoropropyl, or a mixture of methyl and phenyl. In yet another embodiment, M is methoxy, n is 1, R is C alkyl, haloalkyl (such as trifluoropropyl), cyanoalkyl, or aryl (such as phenyl, chlorophenyl or tolyl). 5 It is a divalent C1-C3 aliphatic group, and R is a methyl group.
[0070] The units of formula (5) may be derived from the corresponding dihydroxy polydiorganosiloxane (6):
[0071]
[0072] Among them, R, E, M, R 5 and n are as described above. This dihydroxy polysiloxane can be prepared by a platinum-catalyzed addition reaction between siloxane hydrides represented by formula (7):
[0073]
[0074] Wherein, R and E are as defined above, and aliphatic unsaturated monohydric phenol. Useful aliphatic unsaturated monohydric phenols include, for example, eugenol, 2-allylphenol, 4-allyl-2-methylphenol, 4-allyl-2-phenylphenol, 4-allyl-2-bromophenol, A-allyl-2-tert-butoxyphenol, 4-phenyl-2-phenylphenol, 2-methyl-4-propylphenol, 2-allyl-4,6-dimethylphenol, 2-allyl-4-bromo-6-methylphenol, 2-allyl-6-methoxy-4-methylphenol and 2-allyl-4,6-dimethylphenol. Mixtures containing at least one of the foregoing substances may also be used.
[0075] In one exemplary embodiment, the polysiloxane block is a poly(dimethylsiloxane) (PDMS) block.
[0076] Polysiloxane-polycarbonate can comprise 85-99 % by weight of carbonate units and 1-15 % by weight of siloxane units. Within this range, the polysiloxane-polycarbonate copolymer can comprise 88, 90, 92, 94, 96 or 98 % by weight of carbonate units and corresponding 2, 4, 6, 8, 10 or 12 % by weight of siloxane units. In a specific embodiment, the polysiloxane-polycarbonate comprises 85-98 % by weight of carbonate units and 2-15 % by weight of siloxane units. In another specific embodiment, the polysiloxane-polycarbonate comprises 90-98 % by weight of carbonate units and 2-10 % by weight of siloxane units.
[0077] In one embodiment, the polysiloxane-polycarbonate may comprise a polysiloxane unit and a carbonate unit derived from bisphenol A. The weight average molecular weight of the polysiloxane-polycarbonate is 2000-100000, specifically 5000-50000. The weight average molecular weight is measured by gel permeation chromatography at a sample concentration of 1 mg / mL using a cross-linked styrene-divinylbenzene column and calibrated with a polycarbonate standard.
[0078] The polysiloxane-polycarbonate may have a melt volume flow rate of 1-50 cubic centimeters per 10 minutes (cc / 10 min), specifically 2-30 cc / 10 min, measured at 300° C. and under a load of 1.2 kg. A mixture of polysiloxane-polycarbonates of different flow characteristics may be used to achieve the desired overall flow properties. In one embodiment, an exemplary polysiloxane-polycarbonate is sold under the trade name LEXAN (R) EXL polycarbonate is commercially available from Sabic Innovative Plastics.
[0079] In one embodiment, the aromatic polycarbonate may include recycled polycarbonate.
[0080] Component b)
[0081] The term "laser direct structuring additive" or "LDS additive" is known and is used, for example, in EP2291290B1, US2005064711, WO2005103113 and WO2009024496. In the laser direct structuring process, a thermoplastic composition comprising a thermoplastic resin and a laser direct structuring additive is provided and irradiated with laser radiation on the areas where the conductive tracks are to be formed. Subsequently, the irradiated areas are selectively metallized to form the conductive tracks. Areas not irradiated by the laser radiation do not undergo metallization. The metallization can be performed, for example, by a standard electroless plating process (e.g. a copper plating process).
[0082] Without wishing to be bound by any theory, it is believed that the laser direct structuring additive can be activated by the laser radiation, thereby forming elemental metal particles. It is believed that these metal particles serve as nuclei for copper deposition in a standard electroless copper plating process and as a basis for forming conductive tracks. It is also possible that the radiation is not directly absorbed by the laser direct structuring additive, but is absorbed by other substances, which then transfer the absorbed energy to the laser direct structuring additive, thereby causing the release of elemental metal.
[0083] The laser radiation may be ultraviolet (wavelength from 100 to 400 nm), visible light (wavelength from 400 to 800 nm) or infrared (wavelength from 800 to 25000 nm). Other preferred radiation forms include X-rays, gamma rays and particle beams (electron beams, alpha particle beams and beta particle beams). The laser radiation is preferably infrared light radiation, more preferably having a wavelength of 1064 nm.
[0084] The LDS additive used in the present invention includes copper chromium spinel (e.g., CuCr2O4), or copper chromium manganese oxide spinel (also known as copper-chromium-manganese oxide spinel). Preferably, the LDS additive is CuCr2O4. Copper chromium spinels that can be used as LDS additives include those sold under the trade name LD 5 by Shepherd Technologies.
[0085] Based on the total weight of the composition, the content of component b) in the composition of the present invention is preferably 2-15 wt %, more preferably 4-13 wt %, even more preferably 6-10 wt %, particularly preferably 7-9 wt %.
[0086] Component c)
[0087] The flame retardant is preferably a flame retardant salt or an organic flame retardant.
[0088] The flame retardant salt is preferably a sulfonate, more preferably an alkali metal and / or alkaline earth metal sulfonate. In one embodiment, the composition comprises an alkali metal sulfonate as the sulfonate. Preferably, the composition comprises potassium sulfonate as the sulfonate. More preferably, the composition comprises potassium perfluorobutanesulfonate (PFBS) and / or potassium 3-phenylsulfonylbenzenesulfonate (KSS) as the sulfonate. Even more preferably, the composition comprises potassium perfluorobutanesulfonate as the sulfonate.
[0089] The organic flame retardant is preferably an organic phosphate or phosphazene compound.
[0090] An example of an organophosphate is an aromatic phosphate having the formula (GO)3P=O, wherein each G is independently an alkyl, cycloalkyl, aryl, alkaryl, or aralkyl group, wherein at least one G is an aryl group. Two of the G groups may be linked together to form a cyclic group, for example, diphenylpentaerythritol diphosphate, which is described in U.S. Pat. No. 4,154,775 to Axelrod. Other suitable aromatic phosphates can be, for example, phenyl bis (dodecyl) phosphate, phenyl bis (neopentyl) phosphate, phenyl bis (3,5,5'-trimethylhexyl) phosphate, ethyl diphenyl phosphate, 2-ethylhexyl di (p-tolyl) phosphate, bis (2-ethylhexyl) p-tolyl phosphate, tritolyl phosphate, bis (2-ethylhexyl) phenyl phosphate, tri (nonylphenyl) phosphate, bis (dodecyl) p-tolyl phosphate, dibutylphenyl phosphate, 2-chloroethyl diphenyl phosphate, p-tolyl bis (2,5,5'-trimethylhexyl) phosphate, 2-ethylhexyl diphenyl phosphate or the like. Specific aromatic phosphates refer to phosphates in which each G is aromatic, for example, triphenyl phosphate, tricresol phosphate, isopropylated triphenyl phosphate, etc.
[0091] Also useful are difunctional or polyfunctional aromatic phosphorus-containing compounds, such as compounds of the formula:
[0092]
[0093] Among them, each G 1 is independently a hydrocarbon having 1 to 30 carbon atoms; each G 2 is independently a hydrocarbon or hydrocarbonoxy group having 1-30 carbon atoms; each X is independently bromine or chlorine; m is 0-4, and n is 1-30.
[0094] Examples of suitable difunctional or polyfunctional aromatic phosphorus-containing compounds include resorcinol tetraphenyl diphosphate (RDP), bis(diphenyl) phosphate of hydroquinone and bis(diphenyl) phosphate of bisphenol A, as well as their respective oligomeric and polymeric counterparts, etc. The method for preparing the above difunctional or polyfunctional aromatic compounds is described in British Patent No. 2,043,083.
[0095] A phosphazene compound is an organic compound containing a -P=N bond. Particularly preferred phosphazene compounds include phenoxyphosphazene oligomers (also known as poly(bis(phenoxy)phosphazene)). An example of a phenoxyphosphazene oligomer is Other commercially available preferred phosphazene compounds include those from Otsuka Chemical Co., Ltd. and from Lanyin Chemical Co., Ltd.
[0096] Based on the total weight of the composition, the content of component c) in the composition is 0.05-5% by weight, more preferably 0.1-3% by weight, and more preferably 0.1-2.5% by weight. When component c) is a flame retardant salt, its content is most preferably 0.1-0.3% by weight. When component c) is a phosphazene compound, its content is most preferably 1.5-2.5% by weight.
[0097] In the composition according to the invention, the weight ratio of sulfonate to laser direct structuring additive is preferably at least 0.01:1, more preferably at least 0.015:1, even more preferably at least 0.020:1. In the composition according to the invention, the weight ratio of sulfonate to laser direct structuring additive is preferably at most 0.35:1, more preferably at most 0.30:1.
[0098] Component d)
[0099] The acid-modified polymer may be a polymer obtained by modifying a polymer with a compound having a functional group (for example, an unsaturated carboxylic acid).
[0100] Preferably, the acid-modified polymer is an acid-modified olefin polymer or an acid-modified styrene polymer, more preferably an acid-modified olefin polymer.
[0101] The olefin polymer is preferably polyethylene or polypropylene.
[0102] The weight average molecular weight of the olefin polymer is preferably from 1000 to 5000 g / mol.
[0103] Preferably, the acid-modified polymer is a polymer modified by an unsaturated carboxylic acid, preferably selected from the group consisting of acrylic acid, maleic acid, itaconic acid, maleic anhydride, itaconic anhydride and maleamic acid.
[0104] Most preferably, the acid-modified olefin polymer is maleic anhydride-modified polyethylene. Suitable examples include the commercially available Mitsui Hi-WAX 1105A, manufactured by Mitsui Chemicals, Inc., with an Mv of 1500 and a density of 940 kg / m 3 , the acid value is 60KOHmg / g.
[0105] The content of component d) is 0.1-2.0 wt %, preferably 0.2-1.5 wt %, more preferably 0.4-1.5 wt %, based on the total weight of the composition.
[0106] Component e)
[0107] In aromatic polycarbonate compositions comprising a metal compound capable of being activated by electromagnetic radiation and thus forming an elemental metal core, the presence of a siloxane-based rubber results in reduced or even prevented degradation of the polycarbonate in the composition, as manifested, for example, in increased melt flow stability and / or toughness. Although the presence of such a component is not required in the composition according to the invention, the presence of a siloxane-based rubber can further improve the properties of the composition.
[0108] The silicone-based rubber is preferably a polyorganosiloxane containing a graft copolymer, preferably prepared by polymerizing 5-60 parts by weight of a vinyl monomer (eI) (the sum of (eI) and (e-II) being 100 parts by weight) in the presence of 40-95 parts by weight of polyorganosiloxane particles (e-II), as described in US2005 / 0143520. Examples of the vinyl monomer (eI) include, for example, aromatic vinyl monomers (such as styrene, α-methylstyrene, p-methylstyrene and p-butylstyrene), acrylonitrile monomers (such as acrylonitrile and methacrylonitrile), (meth)acrylate monomers (such as methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, 2-isooctyl acrylate, glycidyl acrylate, hydroxyethyl acrylate, hydroxybutyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, lauryl methacrylate, glycidyl methacrylate and hydroxyethyl methacrylate), and carboxyl group-containing vinyl monomers (such as itaconic acid, (meth)acrylic acid, fumaric acid and maleic acid). If necessary, the vinyl monomer (eI) may include a polyfunctional monomer having at least two polymerizable unsaturated bonds per molecule. Examples of multifunctional monomers include allyl methacrylate, triallyl cyanurate, triallyl isocyanurate, diallyl phthalate, ethylene glycol dimethacrylate, 1,3-butylene glycol dimethacrylate, and divinylbenzene. Vinyl monomer (eI) can be used alone or in combination. Polyorganosiloxane particles (e-II) are preferably prepared by emulsion polymerization of their constituent components. Conventional seed emulsion polymerization can be applied to graft copolymers, and can be achieved by free radical polymerization of vinyl monomer (eI) in an emulsion of polyorganosiloxane particles (e-II).
[0109] These polyorganosiloxane-containing graft copolymers are commercially available, for example, as Kane Ace MR01 and Kane Ace MR02 from Kaneka Corporation.
[0110] Other suitable silicone-based rubbers include Metablen S-2001, Metablen S-2200 and Metablen SX-005 from Mitsubishi Rayon.
[0111] The composition according to the invention does not comprise a methyl methacrylate butadiene styrene (MBS) based rubber. Preferably, the composition according to the invention does not comprise other rubbers than the silicone based rubber (ie component e) as described above.
[0112] Preferably, the content of the silicone rubber (ie component e) as described above is 0-5% by weight relative to the total weight of the composition. More preferably, the content of the silicone rubber is 0-1.5% by weight.
[0113] Component f)
[0114] The thermoplastic composition according to the present invention may further include f) an anti-drip agent.
[0115] Preferably, the content of component f) is 0-2.0 wt % or 0.05-2.0 wt %, more preferably 0.1-1.5 wt %, more preferably 0.2-1.0 wt %, relative to the total weight of the composition. Component f) is optionally present. Therefore, the composition according to the present invention may include little or no component f). For example, the content of component f) is less than 0.05 wt %, less than 0.01 wt % or 0 wt %, relative to the total weight of the composition.
[0116] Suitable examples of anti-drip agents include fluoropolymers, such as polytetrafluoroethylene (PTFE). The fluoropolymer may be a fluoropolymer in fibril form, such as polytetrafluoroethylene (PTFE) in fibril form, or a fluoropolymer in non-fibril form, such as polytetrafluoroethylene in non-fibril form.
[0117] The anti-drip agent may be in the form of a (water) dispersion of a fluoropolymer. In this case, the dispersion contains a sufficient amount of the fluoropolymer, for example the fluoropolymer is at least 30% by weight or at least 50% by weight of the dispersion.
[0118] Anti-drip agent can be the form of the mixture of fluoropolymer and other polymer, for example the fluoropolymer of encapsulation.In this case, dispersion contains enough fluoropolymer, for example fluoropolymer is at least 30 weight % or at least 50 weight % of mixture.Other polymer can be for example acrylate copolymer or styrene-acrylonitrile.The example of the mixture of fluoropolymer and acrylate polymer is METABLEN A-3800 commercially available from MitsubishiRayon Co., Ltd. of Japan.The fluoropolymer of encapsulation can be prepared by polymerizing polymer in the presence of fluoropolymer.
[0119] Preferably, the anti-drip agent is a mixture of a fluoropolymer and another polymer, such as an encapsulated fluoropolymer. Such anti-drip agents can be handled better than anti-drip agents in dispersion form, since they are simpler to feed in an extruder and do not require the removal of water from the composition.
[0120] Component g)
[0121] The thermoplastic composition according to the present invention may further comprise g) 0-10 wt % of one or more other additives (relative to the gross weight of the composition). These include conventional additives, such as stabilizers to prevent thermal or thermo-oxidative degradation, stabilizers to prevent hydrolytic degradation, stabilizers to prevent light (particularly ultraviolet) degradation and / or photo-oxidative degradation, and processing aids, such as mold release agents and lubricants. Suitable examples of these additives and their conventional amounts are described in the Plastics Handbook (Kunststoff Handbuch), 3 / 1. The total amount of additives is typically 0-5 wt %, such as 0.1-3 wt % or 0.3-1 wt %.
[0122] Although the present invention has been described in detail for purposes of illustration, it should be understood that such details are solely for illustrative purposes and variations may be made by those skilled in the art without departing from the spirit and scope of the invention as defined by the claims.
[0123] It should also be noted that the invention relates to all possible combinations of features described herein, with particular preference given to those combinations of features appearing in the claims.
[0124] It should also be noted that the term "comprising" does not exclude the presence of other elements. However, it should also be understood that a description of a product comprising certain components also discloses a product consisting of these components. Similarly, it should also be understood that a description of a method comprising certain steps also discloses a method consisting of these steps.
[0125] The present invention will now be illustrated by the following examples, but is not limited thereto.
[0126] experiment
[0127] The comparative examples (CEx.) and examples (Ex.) summarized in Tables 2-5 were prepared from the components given in Table 1.
[0128] All contents are expressed as weight percent. In each experiment, the sample was extruded using a co-rotating twin-screw extruder at a temperature of 280°C. The extrudate was pelletized and the collected pellets were injection molded into ASTM-sized Izod bars (64×12.7<×>3.2mm) at a melt temperature of about 290°C. The Izod notched impact strength was measured at 23°C and 0°C according to ISO 180 / 4A, and the LVN (intrinsic viscosity number, ISO 1628 / 4) of the molded article was measured. To measure Vicat B50 (Vicat softening temperature at a load of 50N and a heating rate of 50°C / hour according to ISO 306), ISO-sized Izod bars (80×10×4mm) were molded. To measure the UL94 V rating (according to IEC60695-11-10), bars with a thickness of 1.6mm and 3.2mm were molded. MV according to ASTM D3538 standard, at 300℃ and 1500s -1 The measurement was carried out at a shear rate of .
[0129] Table 1
[0130]
[0131]
[0132] Table 2
[0133]
[0134]
[0135] It can be seen that all the examples and comparative examples in Table 2 have a desirable high Vicat softening temperature of 139.0°C or higher, which is ideal for high temperature applications. However, only in the examples according to the present invention can such a high Vicat softening temperature be combined with a combination of other advantageous properties, which will be explained below.
[0136] As can be seen from Comparative Example 1, the MFI of the PC composition increased significantly from 16 dg / min (PC only) to 61.6 dg / min after the addition of CuCr2O4. This is due to the extensive degradation of the polymer. Due to the degradation, the average molecular weight of the polymer chain decreases, thereby increasing the melt flow and resulting in low melt viscosity (MV) and low LVN. As a result, the Izod notched impact strength is also significantly reduced compared to pure PC, which typically has an Izod notched impact strength of more than 70 kJ / m at 23°C. 2 , at -20℃ is about 15-20kJ / m 2 .
[0137] It can be seen from Comparative Example 2 that the addition of Hi-Wax can prevent degradation, where the addition of 0.5 wt% of Hi-Wax stabilizes the MFI at 16.1, the melt viscosity at 168, the LVN at 47, and a relatively high Izod notched impact strength. However, in this case, the flame retardancy (UL-V) shows no rating.
[0138] The increase in the amount of Hi-Wax in Comparative Example 3 resulted in a higher melt viscosity, which is slightly less favorable, although still at an acceptable value. However, as expected, in this comparative example, a UL-V flame retardancy rating is also not shown.
[0139] Adding only flame retardant without adding Hi-Wax, it is possible to obtain a flame retardant composition, see Comparative Example 4. However, in this case, the degree of degradation is very high, as evidenced by the high MFI values and the very low Izod notched impact strength.
[0140] Surprisingly, the combination of flame retardant and Hi-Wax can achieve excellent V1 flame retardancy ratings, as shown in Examples 1 and 2. The combination of Hi-Wax and flame retardant provides a synergistic effect, improving the flame retardancy from V2 level of the individual compositions containing only flame retardant or only Hi-Wax to V1 level of the composition.
[0141] Therefore, adding the flame retardant in combination with the acid-modified polymer can obtain a polycarbonate composition with a suitable melt viscosity (<230 Pa.s), which is suitable for manufacturing thin-walled objects. The polycarbonate composition can form a polycarbonate having a high Vicat softening temperature (>139.0°C), good Izod notched impact strength (>15 kJ / m at -20°C), and good thermal conductivity. 2 ; at 23℃>60kJ / m 2 ) and excellent flame retardancy (V1 grade or V0 grade) of the molded product.
[0142] Table 3
[0143]
[0144] Table 3 provides examples and comparative examples including silicon modifiers. Adding silicon modifiers can improve the flame retardancy from V1 to V0 (comparing Example 3 with Example 1) and / or improve the Izod notched impact strength while having a V1 rating (Example 4). Table 3 further illustrates the changes in results when the LDS additive is changed. Only when CuCr2O4 is used as the LDS additive can a V0 or V1 flame retardancy rating be achieved.
[0145] Table 4
[0146]
[0147] Table 4 shows the results of different blends of virgin polycarbonate and recycled polycarbonate. The viscosity of the virgin polycarbonate was chosen so that the MFI of the PC blend was similar to the previous experiment. All samples had excellent flame retardancy, good flow and strength, which shows that recycled polycarbonate can be used.
[0148] Table 5
[0149] Example 9 Example 10 weight% weight% PC (LVN = 47, MFI = 16) 90.95 90.95 <![CDATA[CuCr2O4]]> 8.00 8.00 FR-Salt 1 0.20 FR-Salt 2 0.20 Heat Stabilizer 0.05 0.05 PTFE1 0.30 0.30 Hi-Wax 0.50 0.50 total 100.00 100.00 MFI@300℃ / 1.2kg dg / min 18.1 18.9 <![CDATA[MV@300℃ / 1500s -1 ]]> Pa.s 198 197 LVN(Mw) ml / g 47 47 Vicat softening temperature ℃ 147.3 147.2 Cantilever beam notch +23°C <![CDATA[kJ / m 2 ]]> 72 71 Cantilever beam notch -20℃ <![CDATA[kJ / m 2 ]]> 44 28 UL@1.5mm - V0 V0
[0150] Finally, as shown in Table 5, compositions using other flame retardants can also provide compositions with excellent flame retardancy as well as good flow and strength.
Claims
1. A thermoplastic composition comprising: a) 85-95% by weight of aromatic polycarbonate; b) 2-15 wt. % of a copper chromium spinel laser direct structuring additive; c) 0.05-5 wt% of a flame retardant, wherein the flame retardant comprises a flame retardant salt or an organic flame retardant; d) 0.1-2 wt% of an acid-modified polymer; e) optionally 0-5% by weight of a silicone-based rubber, wherein the amounts of components a), b), c), d) and e) are based on the total weight of the thermoplastic composition.
2. The composition according to claim 1, wherein The copper-chromium spinel laser direct structuring additive is CuCr2O4.
3. The composition according to claim 1 or 2, wherein The flame retardant salt is a sulfonate, preferably a potassium sulfonate, and more preferably potassium perfluorobutanesulfonate.
4. A composition according to any one of the preceding claims, wherein The organic flame retardant is a phosphazene compound, preferably a phenoxyphosphazene.
5. A composition according to any one of the preceding claims, wherein The acid-modified polymer is an acid-modified olefin polymer; preferably maleic anhydride-modified polyethylene.
6. A composition according to any one of the preceding claims, wherein A molded article of the composition can achieve a UL94 V1 rating or a UL94 V0 rating at a thickness of 1.5 mm (±10%).
7. A composition according to any one of the preceding claims, wherein According to ASTM D3538, at 300°C and 1500s -1 The melt viscosity of the composition is less than 230 Pa.s, preferably less than 210 Pa.s, and more preferably less than 190 Pa.s.
8. A composition according to any one of the preceding claims, wherein According to ASTM D3538, at 300°C and 1500s -1 The melt viscosity of the composition is greater than 40 Pa.s, preferably greater than 70 Pa.s, and more preferably greater than 100 Pa.s.
9. A composition according to any one of the preceding claims, wherein According to ISO180 / 4A standard, at a temperature of 23°C, the Izod notched impact strength of the molded article of the composition is greater than 60 kJ / m 2 , preferably greater than 65 kJ / m 2 , more preferably greater than 70 kJ / m 2 .
10. A composition according to any one of the preceding claims, wherein According to ISO180 / 4A standard, at a temperature of -20°C, the Izod notched impact strength of the molded article of the composition is greater than 15 kJ / m 2 , preferably greater than 20 kJ / m 2 , more preferably greater than 25 kJ / m 2 .
11. A composition according to any one of the preceding claims, wherein According to ISO 306 standard, at a load of 50 N and a heating rate of 50° C. / h, the Vicat softening temperature of a molded article of the composition is higher than 130° C., preferably higher than 135° C., more preferably higher than 139° C.
12. A molded article comprising the composition according to any one of claims 1 to 11.
13. A method for producing a circuit carrier, comprising: Providing a molded article as claimed in claim 12; irradiating the area of the molded article where the conductive track is to be formed with laser radiation; and then metallizing the irradiated area.
14. A circuit carrier obtained according to the method as claimed in claim 13.
15. An antenna comprising the circuit carrier according to claim 14.
Citation Information
Patent Citations
Flame retardant laser direct structuring materials
EP2291290B1
Flame retardant polyphenylene ether compositions
GB2043083A
Oriented, aminosilane-coated film capable of structuring by means of electromagnetic radiation and composed of thermoplastic polyester for the production of selectively metallized films
US20050064711A1
Polyorganosiloxane-containing graft copolymer composition
US20050143520A1
Flame retardant composition of polyphenylene ether, styrene resin and cyclic phosphate
US4154775A